2015
DOI: 10.1186/s13568-015-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial inhibition of oral epithelial wound recovery: potential role for quorum sensing molecules?

Abstract: Awareness of the impact of microbiota in both health and disease is growing. Using a new in vitro oral mucosa co-culture model, we recently showed a clear inhibition of epithelial wound healing in the presence of an oral microbial community. In this paper, we have used the same model in combination with specific oral microbial species to obtain a better insight into the role of the oral microbiota in wound healing. Monocultures of Klebsiellaoxytoca and Lactobacillus salivarius significantly inhibited wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…28,[38][39][40] On the other hand, L. salivarius and L. plantarum inhibited oral epithelial wound healing. 41 A recent study showed that a bioengineered L. reuteri with a plasmid encoding CXCL12 accelerated cutaneous wound healing in mouse, while nontransformed L. reuteri delayed wound closure. 42 In the present study, we demonstrated that 43 L. crispatus and its supernatant decreased proinflammatory cytokines and increased IL-10 production by HeLa cells in the presence of Chlamydia trachomatis.…”
Section: Discussionmentioning
confidence: 99%
“…28,[38][39][40] On the other hand, L. salivarius and L. plantarum inhibited oral epithelial wound healing. 41 A recent study showed that a bioengineered L. reuteri with a plasmid encoding CXCL12 accelerated cutaneous wound healing in mouse, while nontransformed L. reuteri delayed wound closure. 42 In the present study, we demonstrated that 43 L. crispatus and its supernatant decreased proinflammatory cytokines and increased IL-10 production by HeLa cells in the presence of Chlamydia trachomatis.…”
Section: Discussionmentioning
confidence: 99%
“…The desalted samples were divided in two equal volume aliquots, one of which was treated with 200 μg/ml proteinase K (1 hour at 37 °C) and the other was left untreated. Inactivation of proteinase K was accomplished by heating the samples to 98 °C for 10 minutes, followed by centrifugation (16,000 × g, 10 min at room temperature) 62 . After centrifugation, all samples were filtered sterilized (0.2 μm, Whatman, GE Healthcare Life Sciences) and then stored at −80 °C until used.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on oral epithelial wound recovery, De Ryck and colleagues already pointed out that K. oxytoca must secret other effector molecules beyond tilivalline and tilimycin. They hypothesized that K. oxytoca -produced quorum-sensing molecules might contribute to its inhibitory impact on wound healing [24]. Former studies showed the toxicity of culture supernatant of K. oxytoca derived from patients with AAHC was not inactivated by 60 °C treatment, but was sensitive to 100 °C [25].…”
Section: Discussionmentioning
confidence: 99%